Energetics of a Novel 3D-Printed Custom Ankle Foot Orthosis in a Population of Individuals with Foot Drop: A Pilot Study - Paolo Caravaggi; Giulia Rogati; Massimiliano Baleani; Roberta Fognani; Luca Zamagni; Maurizio Ortolani; Alessandro Zomparelli; Franco Cevolini; Zimi Sawacha; Alberto Leardini (Applied Sciences)
Passive Dynamic Ankle–Foot Orthoses (PD-AFOs) are medical devices prescribed to individuals with foot drop, a condition characterized by weakness of the ankle dorsiflexor muscles. PD-AFOs can store and release energy during the stance phase of the gait cycle, while supporting the foot in the swing phase. This study aimed at estimating the energetics of a novel fiberglass-reinforced polyamide custom PD-AFO in a population of mild foot drop patients. Eight PD-AFOs were designed and 3D-printed via selective laser sintering for eight participants with a unilateral foot drop condition. Lower limb kinematics and AFO flexion/extension were recorded during comfortable walking speed via skin marker-based stereophotogrammetry. The stiffness of each AFO was measured via an ad hoc experimental setup. The elastic work performed by the PD-AFO during gait was calculated as the dot product of the calf-shell resisting moment and the rotation angle. The average maximum energy stored by the calf-shell across all PD-AFOs was 0.013 ± 0.005 J/kg. According to this study, 3D-printed custom PD-AFOs made with fiberglass-reinforced polyamide can store some elastic energy, which is released to the ankle during push-off. Further studies should be conducted to assess the effect of this energy return mechanism in improving the gait of individuals with deficits of the ankle plantarflexor muscles.